Are Oaks Locally Adapted to Serpentine Soils? - Branco, Sara (Northeastern Naturalist, 2009)
Serpentine soils are extreme habitats known to be involved in processes of local adaptation and speciation of plants. Here I use a greenhouse reciprocal-transplant experiment to compile baseline data for describing patterns of serpentine local adaptation in Quercus ilex subsp. ballota (Holm Oak). I also tested the role of mycorrhizal fungi on the establishment and growth of seedlings on serpentine and non-serpentine soil. Non-serpentine seedlings grew more than serpentine seedlings in all treatments. Plants grew more on non-serpentine soil and mycorrhizal fungi positively influenced seedling growth. I did not find evidence of better seedling performance in their home environment, suggesting the absence of local adaptation. However, I document significant growth differences between serpentine and non-serpentine seedlings, which suggest physiological differences between seedlings from these two soil origins.
doi: 10.1656/045.016.0524doi: 10.1656/045.016.0524The following values have no corresponding Zotero field: publisher: Eagle Hill Institute
Keywords: Mycorrhizal fungi; seedling growth (PG); serpentine

Vegetation of tuscan ultramafic soils in relation to edaphic and physical factors - Chiarucci, Alessandro; Robinson, Brett H.; Bonini, Ilaria; Petit, Daniel; Brooks, Robert R.; Dominicis, Vincenzo (Folia Geobotanica, 1998)
Vegetation and soil sampling were carried out in 80 plots located in five different ultramafic (serpentine) sites of Tuscany, central Italy. The physical and chemical features of each plot. were determined and the species composition and cover recorded. The exchangeable fraction of soil metals was analysed because it gives a measure of their concentrations available to plants. The plots were classified by cluster analysis and ANOVA was used to compare the environmental variables of the groups of plots. Canonical correspondence analysis was used to detect the principal factors for gradients of species composition within the plant communities. A higher content of exchangeable metals was found under the more evolved and structured plant communities, suggesting that serpentine vegetation of Tuscany is not strongly limited by soil metals, such as chromium, cobalt, nickel and magnesium, typically associated with ultramafic soils. The low nutrient content of the soils and drought stress mainly due to topographical features, appear to have a more significant role in determining the typical scattered vegetation of the Tuscan ultramafics.
Keywords: canonical correspondence analysis; Drought; serpentine; soil features; species diversity; vegetation ecology